Absorption-based quantum communication with NV centres. (8th October 2015) - Scharfenberger, Burkhard; Kosaka, Hideo; Munro, William J; Nemoto, Kae
Abstract: We propose a scheme for performing an entanglement-swapping operation within a quantum communications hub (a Bell like measurement) using an NV-centre's optical transition. This is based on the heralded absorption of a photon resonant with that transition. The quantum efficiency of a single photon absorption is low but can be improved by placing the NV centre inside a micro cavity to boost the interaction time and further by recycling the leaked photon back into the cavity after flipping its phase and/or polarization. Throughout this process, the NV is repeatedly monitored via a QND measurement that heralds whether or not the photon absorption has succeeded. Upon success we know a destructive Bell measurement has occurred between that photon and NV centre. Given low losses and high per-pass absorption probability, this scheme should allow the total success probability to approach unity. With long electron spin coherence times possible at low temperatures, this component could be useful within a memory-based quantum repeater or relay.